Quality of life of survivors following road traffic orthopaedic injuries in Rwanda - Allen Ingabire, J. C.; Tumusiime, David K.; Sagahutu, Jean Baptiste; Urimubenshi, Gerard; Bucyibaruta, Georges; Pilusa, Sonti; Stewart, Aimee (Frontiers in Public Health, 2024)
Background Road traffic injuries (RTI) pose a global public health threat, especially in low- and middle-income nations. These injuries typically cause orthopaedic problems that may negatively impair a person’s physical and mental health and quality of life. Our study examined the quality of life of road traffic orthopaedic injuries (RTOI) survivors. Methods A cross-sectional study at five Rwandan referral hospitals, included 369 adult RTOI victims. Two years post-injury, participants completed the European Quality of life 5 Dimension 5 (EQ-5D-5L) and Visual Analogue Scale (VAS) Questionnaire between June 2 and August 31, 2022, with informed consent. Three EQ-5D-5L-VAS scores were used: low (0–40%), fair (41–60%), and excellent (61–100%). We used logistic regression analysis with a significance threshold of p < 0.05 to determine odds ratios (OR) and 95% CI. Results The RTOI victims had a mean age of 37.5 ± 11.26 years with sex ratio M:F:3:1. Usual activities (66.8%) and mobility (54.8%) were the most affected EQ-5D-5L dimensions. Residence, hospital stay, rehabilitation, and return to work affected mobility, usual activities, pain/discomfort, and anxiety/depression. The EQ-5D-5L/VAS score showed 34.95% poor QoL (0–40%) and 35.50% good QoL. Factors affecting QoL include level of education (OR = 1.66, p < <0.01), type of intervention (OR = 1.22, p = 0.003), rehabilitation (OR = 2.41, p < 0.01) and level of disability (OR = 196.41, p < 0.01). Mobility, self-care, usual activities, pain, comfort, anxiety, and depression vary moderately on Shannon’s index. Conclusion The study highlights the significant impact of road traffic orthopaedic injuries (RTOI) on survivors’ quality of life in Rwanda, revealing challenges in mobility and daily activities. Factors influencing quality of life include education level, medical intervention type, rehabilitation, and disability degree. The findings emphasize the need for tailored rehabilitation strategies and policy interventions to improve long-term outcomes for RTOI survivors.